(untitled) (Economics and region, 2025)
The article is devoted to the issue of the effectiveness of public administration bodies in ensuring economic security in the face of global challenges and threats. It is determined that the economic security of the state is a complex multidimensional phenomenon that encompasses financial stability, energy independence, resilience to crisis events and the ability to achieve economic growth in the face of globalization. The global challenges and threats that arise in the sphere of economic security of the state in modern conditions are considered. The challenges are noted and recommendations are substantiated for increasing the effectiveness of public administration bodies in the sphere of economic security of the Ukrainian state. The key role of food and industrial security as important components of the state’s economic security is emphasized. It is noted that modern challenges and threats require increased attention to production and, in particular, industrial security, since it is industry that provides the country’s critically important needs, in particular the production of defense products, dual-use products, as well as basic materials for infrastructure restoration. The key role of the Ministry of Economy of Ukraine in reducing risks to the economic security of the state is emphasized, as well as the need to involve state, scientific and public institutions in comprehensive cooperation to effectively respond to challenges to economic security. It is concluded that the economic security of the Ukrainian state should be strengthened through such strategic areas as improving the activities of public administration bodies to ensure economic security and developing a unified state strategy, introducing innovative management methods, strengthening interdepartmental coordination, increasing the level of transparency and combating corruption. It is emphasized that the implementation of the proposed measures will strengthen the economic stability of the state, increase the efficiency of management decisions and promote stable socio-economic development in the long term.